Determination of the Possibilities of Using Wood and Hazelnut Vinegar in the Control of Harmful Mealy Lice Planococcus ficus Signoret (Hemiptera: Pseudococcidae) in Vineyards of Elazig Province - Aytac, Sevcan; Cakir, Veysel (Mdpi, 2025)
The background of this study is grounded in the economic importance of Planococcus ficus (P. ficus) Signoret (Hemiptera: Pseudococcidae), commonly known as the vine mealybug, which is a major pest in vineyards across South Africa, the Mediterranean region, the Middle East, Argentina, California, and Mexico. This pest causes both direct damage to grapevines and indirect damage by promoting the development of sooty mold, which reduces fruit quality and marketability. The limited effectiveness of conventional pesticides-due to the pest's concealed habitats and biological resistance-combined with their negative impacts on beneficial arthropods, underscores the need for alternative and environmentally sustainable pest management approaches. The methodology of this study involved a field trial conducted in Koruk Village, Elaz & imath;& gbreve; Province, Turkey, from March to October 2022. The aim of the study is to determine the repellent and toxic effects of two types of wood vinegar (WV) and hazelnut vinegar (HV) on P. ficus populations under natural vineyard conditions by using statistical data analysis methods used in basic engineering. Various concentrations of each vinegar wereapplied to the vines, and pest population dynamics were monitored. Additionally, the potential repellent effects of the vinegars on beneficial predatory insects, particularly members of the Coccinellidae family, were assessed. The results of the study indicated that wood vinegar (WV) was more effective than hazelnut vinegar (HV) in reducing P. ficus populations. Both vinegars demonstrated statistically significant, dose-dependent reductions in pest numbers compared to the untreated control. Although both treatments also exhibited repellent effects on Coccinellidae species, these effects were not statistically significant when compared with the positive control group. These findings support the potential application of vinegar-based products in integrated pest management. The conclusion of this study is that wood vinegar (WV) and hazelnut vinegar (HV), as natural carbonization-derived products, can serve as environmentally friendly alternatives for controlling P. ficus in vineyards. Their application may reduce reliance on synthetic pesticides, contribute to sustainable viticulture practices, and minimize negative impacts on non-target beneficial organisms. This research introduces an innovative, eco-compatible control that could be effectively integrated into broader Integrated Pest Management (IPM) strategies.
Keywords: vineyard; Planococcus ficus; herbal insecticide; wood-hazelnut vinegar